Caregivers' perceptions, challenges and service needs related to tackling childhood overweight and obesity: a qualitative study in three districts of Shanghai, China - Yanting Wu; Xiaoying Ma; William D. Fraser; Mu Li; Wei Wang; Hefeng Huang; Myriam Landry; Yanhui Hao; Han Liu; Sonia Semenic; Yan Zhang; Haiqin Wang; et al. (BMC, 2021)
Abstract Background Childhood overweight and obesity (OWO) has become a major public concern worldwide including in Shanghai, one of the most developed areas of China. Understanding perceptions and challenges of tackling childhood OWO among caregivers of children is critical to provide services in need. Methods A qualitative descriptive study including in-depth interviews with seven parents and six focus group discussions with a total of 32 parents or grandparents of children zero to 6 years of age. Participants lived in three districts of Shanghai and indexed children included both those with OWO or non-OWO children. Data were analyzed using qualitative thematic analysis. Results Caregivers tended to underestimate children's weight status, and to regard chubby children as a sign of good parental care. Some caregivers even suggested that there were positive effects of childhood overweight. Caregivers identified a number of challenges to prevention of OWO in children, including difficulties in controlling dietary intake or increasing children's physical activities; discordant views between parents and grandparents, and barriers to accessing professional guidance. Caregivers desired more detailed advice regarding children's nutrition intake and physical activity, and preferred online approaches. Conclusions Misconceptions regarding childhood overweight were found in caregivers of children in Shanghai. Professional guidance on childhood weight control for caregivers is desired via digital applications such as mobile phone applications and social media.